PERSEPSI GURU TENTANG PENYEDERHANAAN KURIKULUM 2013 MASA PANDEMI COVID-19 DALAM MATA PELAJARAN SEJARAH TAHUN AJARAN 2020/2021 DI SMAN 1 SUNGAI RUMBAI DAN SMAN 2 SUNGAI RUMBAI - Zanelia Nafendani; Liza Husnita; Jaenam Jaenam (Universitas Pahlawan, 2021)
This research is motivated by the implementing the emergency curriculum during the pandemic in history learning. The problem of this research is the teacher's perception of the simplification of the 2013 curriculum during the pandemic period in history subjects for the 2020/2021 academic year at SMAN 1 Sungai Rumbai and SMAN 2 Sungai Rumbai. The purpose of this study is to describe Teacher Perceptions About the Simplification of the 2013 Pandemic Curriculum in History Subjects for the 2020/2021 Academic Year at SMA N 1 Sungai Rumbai and SMA N 2 Sungai Rumbai. The method used is descriptive qualitative method. This research uses the Stimulus Response theory, a theory that emphasizes the response or response to something that happens such as a policy or rule. The data collection techniques used are: 1) Observation, 2) Interview, 3) Documentation Study. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study found that Teacher Perceptions About Simplification of the 2013 Pandemic Curriculum in History Subjects for the 2020/2021 Academic Year at SMAN 1 Sungai Rumbai and SMAN 2 Sungai Rumbai were effectively used during pandemic learning. This is based on the tendency of teachers to view the emergency curriculum which has reduced lesson hours and material exposure so that it can make it easier for students and teachers in learning activities during the pandemic.